Arsip sebagai kendali intelektualitas dalam proses produksi pengetahuan - Arif Rahman Bramantya (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. Archives are not only seen as a product but also as a process to produce knowledge particularly, through interdisciplinary collaborations in the era of postmodernisme. The postmodernism perspective may influence the interpretation of archives which leads to archival discourse. This study aims to investigate the postmodernism perspective of archives in the knowledge production process in a more impartial and democratic way. Data Collection Methods. This study used a qualitative approach through literature study. Results and Discussion. The postmodernism perspective has opened up new viewpoints on the role and function of archives in the knowledge production process for searching and reading archives in a more diverse manner. In this study, several discussed archives were related to human rights, community engagement, accountability, and power relations, as well as social and transitional justice. The postmodernism perspective of archives as intellectual control in the production of knowledge through interdisciplinary collaboration and as one of the sustainable international projects may establish intellectual networks between countries. Conclusion. The postmodernism perspective has provoked new ideas and expanded the discourse on archives needed in the development of the archival field. Archivists as well as historians play a new role as users of archives who have a responsibility in intellectual control to write democratic historical narratives.